Growth in Colombian Municipalities: The Role of Spatial Externalities, the Human Capital and Physical Capital - Galvis-Aponte, Luis Armando; Hahn-De-Castro, Lucas Wilfried (Sociedad y Economía, 2016)
In this paper we analyse economic growth in Colombian municipalities during the period1993-2012. The aim is to evaluate the existence of convergence taking into accountthe externalities of physical and human capital. According to Mankiw Romer & Weil(1992), we estimate convergence equations that are augmented with human capital. Wefollow the methodology proposed by Ertur and Koch (2006, 2007), who include technologicalexternalities in the analysis of the model which solely considers physical capital(Solow 1956), and the augmented model with human capital. The results show that whenspillovers are not taken into account, there is evidence of convergence; however suchevidence disappears when these effects are added to the model.